Survival analysis of COVID-19 outcomes in pregnant and non-pregnant women: A secondary data study - Retnaningsih, Listyana Natalia; Fadlilah, Siti; Suharto, Agus; Widaryanti, Rahayu; Sugimoto, Hiroshi; Arifin, Hidayat (Pediomaternal Nursing Journal, 2025)
Introduction: Pregnant women are a population vulnerable to health problems. The morbidity and mortality of pregnant women with COVID-19 are higher compared with the rest of the population. This study aims to determine the survival rate of pregnant versus non-pregnant women with COVID-19. Methods: The study used a retrospective observational cohort design. Data were collected from Dr Soeradji Tirtonegoro and Penembahan Senopati hospitals on patients treated between March 2020 and June 2022. A total of 923 women diagnosed with COVID-19 were included in the study. Sociodemographic and clinical data on patient characteristics were extracted from medical records. Data analysis was conducted using Kaplan-Meier and Cox regression analyses to estimate survival probability and investigate predictors of death, with a 5% significance level. Results: Among 932 women with COVID-19, 231 deaths occurred. The median survival time for all participants was 30.56 days, while for pregnant women, it was 11.21 days, and for pregnant women with comorbidities, it was 9.68 days. Years of treatment, age, comorbidities, number of comorbidities and pregnancy were associated with survival rate (P-value < 0.001). Consistent results were also obtained for pregnant women’s age and number of comorbidities (P-value < 0.05). Significant differences between pregnant and non-pregnant patients remained after adjustment for year, sex, age and hospital type (P-value < 0.001). Conclusion: Pregnant women with COVID-19 have a higher risk of death compared with non-pregnant women. Keywords: comorbidity; COVID-19, female; pregnant women; survival analysis